2020
DOI: 10.1105/tpc.20.00252
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Pectin Methyltransferase QUASIMODO2 Influence Cellulose Biosynthesis and Wall Integrity in Arabidopsis

Abstract: Physical and functional interactions between pectin and cellulose are required for normal wall assembly and plant growth, as revealed in analyses of mutants for a pectin methyltransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 108 publications
(152 reference statements)
2
91
0
Order By: Relevance
“…However, the mutants also displayed reduced cellulose crystallinity, hypersensitivity to isoxaben, and radial expansion, which are typical for cellulose biosynthetic mutants. Moreover, it was shown that the transcript levels of FEI1 and FEI2 were significantly reduced in pectin-deficient qua2 mutants [39], which was interpreted as evidence of an important role of pectin in controlling cellulose deposition. Furthermore, it was shown that loss of function mutations in the SHOU4 and SHOU4L loci (shou meaning 'slim in Chinese) that encode novel membrane proteins partially suppressed the fei1 fei2 phenotype and increased cellulose deposition.…”
Section: The Fla4-fei Pathway Genetically Interacts With Primary Cellmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the mutants also displayed reduced cellulose crystallinity, hypersensitivity to isoxaben, and radial expansion, which are typical for cellulose biosynthetic mutants. Moreover, it was shown that the transcript levels of FEI1 and FEI2 were significantly reduced in pectin-deficient qua2 mutants [39], which was interpreted as evidence of an important role of pectin in controlling cellulose deposition. Furthermore, it was shown that loss of function mutations in the SHOU4 and SHOU4L loci (shou meaning 'slim in Chinese) that encode novel membrane proteins partially suppressed the fei1 fei2 phenotype and increased cellulose deposition.…”
Section: The Fla4-fei Pathway Genetically Interacts With Primary Cellmentioning
confidence: 96%
“…While cellulose and hemicellulose on the one hand and pectin on the other hand have previously been depicted as forming largely independent networks in the cell wall [36,37], the biomechanical hotspot model suggests a close association between all three groups of biopolymers in biomechanically critical microdomains [38]. A recent example of the physiological link between pectin and cellulose was the demonstration that the QUASIMODO2 (QUA2) locus, which primarily acts in pectin biosynthesis, also had a great impact on cellulose biosynthesis and crystallinity [39]. Moreover, to reinforce the cell wall in situations of biotic and abiotic stress, crosslinking of cell wall glycoproteins, such as extensins and arabinogalactan proteins, by cell wall peroxidases might play an important conditional role [40][41][42].…”
Section: The Fla4-fei Pathway Genetically Interacts With Primary Cellmentioning
confidence: 99%
“…The same plants not only express high levels of OG-oxidases but also an oxidase acting on CDs (Locci et al, 2019). Notably, recent studies show that cellulose and pectin interact (Du et al, 2020;Palacio-Lopez et al, 2020) and that cellulose microfibers and HG nanofilaments form a single cohesive network (Haas et al, 2020;Zhang and Zhang, 2020).…”
Section: Final Considerations: the Role Of Oxidases In The Maintenancmentioning
confidence: 99%
“…There is crosstalk between cell wall components (12). For example, plants with a defect in hemicellulose production or in the pectin methylation exhibit reduced cellulose content (58, 59). Indeed, we found that SUB activity is downregulated upon application of epigallocatechin gallate (EGCG), an inhibitor of pectin methylesterase activity (60), to seven-day-old seedlings leading.…”
Section: Discussionmentioning
confidence: 99%